Service co-production and value co-creation: The case for a service-oriented architecture (SOA) - Ordanini, Andrea; Pasini, Paolo (European management journal, 2008)
An emerging marketing management logic proposes a new perspective on service activities, which previously have been subject to a biased goods-dominant logic. According to this new logic, customers always are co-producers of services and co-creators of value, not simple marketing targets, because they mobilize knowledge and other resources in the service process that affect the success of a value proposition. This article explores this key proposition, analyzing service co-production and value co-creation phenomena in the business-to-business segment and focusing on the case of service-oriented architecture (SOA) with an in-depth, qualitative analysis of two firms pioneering the implementation of SOA solutions.